IMPLEMENTING GENDER MAINSTREAMING (PUG) POLICY IN THE EDUCATION SECTOR: AN ANALYTICAL STUDY OF PRIVATE SECONDARY SCHOOL - Nasution, Annisa Ramadani; Junita, Audia; Nasution, Chairika (Pena Cendekia Insani, 2026)
Gender mainstreaming is a strategic policy for integrating gender equality into educational governance and practice. This study examines how Gender Mainstreaming (PUG) policy is implemented in a private secondary school, SMP Swasta IT Al Fajar Tanjung Morawa, Indonesia, and identifies the factors that support and constrain its implementation. Using a qualitative descriptive design, data were collected through in-depth interviews, field observation, and document review involving ten purposively selected informants, namely the principal, vice principal for student affairs, guidance and counseling teacher, teachers, students, administrative staff, and parents. Guided by policy implementation theory, the study finds that gender mainstreaming is practiced mainly as a moral commitment to fair treatment rather than as a formal and measurable institutional policy. Although school actors generally support gender equality, implementation remains limited by the absence of technical guidelines, gender-responsive planning, dedicated budget allocation, and sex-disaggregated data. The analytical novelty of this study lies in its focus on a private secondary school, a setting that is often underexplored despite having different supervision patterns, institutional autonomy, and resource conditions from public schools. The findings show that private-school cases are important for understanding how national gender policy is translated unevenly at the micro-institutional level. Strengthening internal policy instruments, organizational capacity, and monitoring systems is therefore crucial for advancing sustainable gender-responsive school governance.